The Influence of Competence, Motivation, and Work Environment on Employee Performance in Financial Services - Rosita Rosita; Anton Anton; Dennis Widjaja (Jurnal Ilmiah Multidisiplin, 2026)
This study examines the effects of competence, work motivation, and work environment on employee performance in financial service companies in Yogyakarta. A quantitative approach with a descriptive and verification survey design was employed. The study population consisted of 145 permanent employees, from whom 100 respondents were selected using simple random sampling. Data were collected through a questionnaire using a five-point Likert scale and analyzed with IBM SPSS Statistics Version 26. The analytical procedures included validity and reliability testing, classical assumption testing, multiple linear regression, partial t-tests, simultaneous F-tests, and the coefficient of determination. The results demonstrate that competence has a positive and significant effect on employee performance. Work motivation and work environment also positively and significantly influence employee performance. Simultaneously, the three independent variables significantly affect employee performance, explaining 72.6% of its variation, while the remaining 27.4% is associated with factors outside the research model. Competence is identified as the most dominant predictor of employee performance. These findings indicate that employee performance can be improved through integrated human resource policies that strengthen professional competence, enhance work motivation, and create a safe, supportive, and conducive work environment. This study provides practical evidence for financial service company management in designing employee development, reward, and workplace improvement programs.